Design Earthquake Response Spectrum Affected by Shallow Soil Deposit - Dong-Kwan Kim; Hong-Gun Park; Chang-Guk Sun (Advances in Civil Engineering)
Site response analyses were performed to investigate the earthquake response of structures with shallow soil depth conditions in Korea. The analysis parameters included the properties of soft soil deposits at 487 sites, input earthquake accelerations, and peak ground-acceleration levels. The response spectra resulting from numerical analyses were compared with the design response spectra (DRS) specified in the 2015 International Building Code. The results showed that the earthquake motion of shallow soft soil was significantly different from that of deep soft soil, which was the basis of the IBC DRS. The responses of the structures were amplified when their dynamic periods were close to those of the site. In the case of sites with dynamic periods less than 0.4 s, the spectral accelerations of short-period structures were greater than those of the DRS corresponding to the site class specified in IBC 2015. On the basis of these results, a new form of DRS and soil factors are proposed.